Yan Amos Komenskiyning pedagogik sistemasi - Sobirova Marjona Shavkat qizi, Yuldasheva Parvina Rustam qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
In this article, Garbiy made a significant contribution to the development of the science of pedagogy Pedagogical views of the European scientist Jan Amos Comenius, in his works the purpose of education is to conduct education in harmony with nature his thoughts and ideas about the socio-political situation of the time he lived such topics as the influence of the environment are covered.